Are there gender differences in acute management and secondary prevention of acute coronary syndromes in Barbados? A cohort study. Issue 1 (28th January 2019) - Sobers, Natasha; Rose, Angela M C; Samuels, T Alafia; Critchley, Julia; Abed, Melissa; Hambleton, Ian; Harvey, Arianne; Unwin, Nigel
Abstract : Objectives: In Barbados, high case fatality rates have been reported after myocardial infarction (MI) with higher rates in women than men. To explore this inequality, we examined documented pharmacological interventions for ST-segment elevated myocardial infarction (STEMI), non-STEMI (NSTEMI) and unstable and chronic angina in women and men. Design: Prospective cohort registry data for STEMI and NSTEMI and retrospective chart review for unstable and chronic angina. Setting: Tertiary care (acute coronary syndromes) and primary care (chronic angina) centres in Barbados. Participants: For the years 2009–2016, a total of 1018 patients with STEMI or NSTEMI were identified via the prospective study. For unstable and chronic angina, 136 and 272 notes were reviewed respectively for the years 2010–2014. Outcome measures: The proportions of patients prescribed recommended medication during the first 24 hours after an acute event, at discharge and for chronic care were calculated. Prescribed proportions were analysed by gender after adjustment for age. Results: Between 2009 and 2016, for the acute management of patients with NSTEMI and STEMI, only two (aspirin and clopidogrel) of six drugs had documented prescription rates of 80% or more. Patients with STEMI (n=552) had higher prescription rates than NSTEMI (n=466), with gender differences being more pronounced in the former. Among patients with STEMI, after adjustment for age, diabetes, hypertension and smoking, men were more likely to receive fibrinolytics acutely, OR 2.28 (95% CI 1.24 to 4.21). Compared with men, a higher proportion of women were discharged on all recommended treatments; this was only statistically significant for beta-blockers: age-adjusted OR 1.87 (95% CI 1.16 to 3.00). There were no statistically significant differences in documented prescription of drugs for chronic angina. Conclusion: Following acute MI in Barbados, the proportion of patients with documented recommended treatment is relatively low. Although women were less likely to receive appropriate acute care than men, by discharge gender differences were reversed.